2007
DOI: 10.1109/tpwrd.2006.881439
|View full text |Cite
|
Sign up to set email alerts
|

Traveling-Wave-Based Fault-Location Scheme for Multiend-Aged Underground Cable System

Abstract: This paper presents a novel wavelet-based fault-location scheme for aged cable systems when synchronized digital fault recorded data are available at the two terminals of each cable. The proposed scheme estimates the fault location in multiend-aged cable systems using the theory of wavelet singularity detection as a powerful signal processing tool. The arrival of the first and second voltage traveling waves at both ends of the power cables can be identified reliably. The developed wavelet processing scheme is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(40 citation statements)
references
References 11 publications
1
39
0
Order By: Relevance
“…In a recent paper [50], it is suggested that the wave velocity can be eliminated from Eq. 2.1 and 2.2 by combining the two methods.…”
Section: Chapter 2 -Fault In Transmission Cables and Current Fault Lomentioning
confidence: 99%
“…In a recent paper [50], it is suggested that the wave velocity can be eliminated from Eq. 2.1 and 2.2 by combining the two methods.…”
Section: Chapter 2 -Fault In Transmission Cables and Current Fault Lomentioning
confidence: 99%
“…2 shows the reflection and refraction of the travelling wave between the bus and the fault point when a fault occurs near M side. When there are more than three incoming lines and outgoing lines on a bus, the wave impedance of the bus is far less than that of the cable, the reflection coefficient at the bus and the refraction coefficient at the fault point are both positive, therefore, the law of the modulus maxima concluded in [15][16] is that the modulus maxima of the initial wave and the reflected wave have the same polarity, while that of the refracted wave from the remote end is opposite to the formers; moreover, the value of the maxima represents the energy of the travelling wave, which attenuates during the propagation gradually.…”
Section: B the Propagation Characteristics Of The Travelling Wave Onmentioning
confidence: 99%
“…The method reported in [2] uses multi end system to locate the fault in power cable lines by using wavelet transform to collect the high frequency signals. However, the method mentioned in [2] uses the sampling frequency which is quite high and difficult for practical implementation.…”
Section: Introductionmentioning
confidence: 99%